A Pesantren Cultural Value-Based Learning Model: Integrating Islamic Values and 21st-Century Skills - Fahrudin, Ahmad; Khoirul Malik, Muhammad (IAIN Ponorogo, 2025)
This study investigates the need for an educational model that bridges traditional pesantren cultural values with the demands of 21st-century education. The research addresses the gap in current educational practices that often neglect integrating character-based Islamic values with contemporary life skills and technological competence. Researchers used a qualitative research approach in field studies. Data collection used observation, in-depth interviews, and documentation. Data validity was ensured through source, methodological, and time triangulation. Then, the data were analyzed using Miles, Huberman, and Saldana's (2014) interactive model, consisting of data condensation, data display, and conclusion drawing. The findings of this study lie in its innovative approach to integrating traditional pesantren values with modern 21st-century skills, focusing on character building, practical life skills, and the use of information and communication technology (ICT) to improve educational outcomes. This integration aims to create a holistic and relevant education model for contemporary times.